Using phase interference to characterize dynamic properties—a review of constant gradient, portable magnetic resonance methods - Selby, William; Balcom, Bruce J.; Newling, Benedict; Mastikhin, Igor (Frontiers in Physics, 2023)
Spatially resolved motion-sensitized magnetic resonance (MR) is a powerful tool for studying the dynamic properties of materials. Traditional methods involve using large, expensive equipment to create images of sample displacement by measuring the spatially resolved MR signal response to time-varying magnetic field gradients. In these systems, both the sample and the stress applicator are typically positioned inside a magnet bore. Portable MR instruments with constant gradients are more accessible, with fewer limitations on sample size, and they can be used in industrial settings to study samples under deformation or flow. We propose a view in which the well-controlled sensitive region of a magnet array acts as an integrator, with the velocity distribution leading to phase interference in the detected signal, which encodes information on the sample's dynamic properties. For example, in laminar flows of Newtonian and non-Newtonian fluids, the velocity distribution can be determined analytically and used to extract the fluid's dynamic properties from the MR signal magnitude and/or phase. This review covers general procedures, practical considerations, and examples of applications in dynamic mechanical analysis and fluid rheology (viscoelastic deformation, laminar pipe flows, and Couette flows). Given that these techniques are relatively uncommon in the broader magnetic resonance community, this review is intended for both advanced NMR users and a more general physics/engineering audience interested in rheological applications of NMR.